Branding Management of Sido Muncul Product (Case Study of TolakAngin) and Its Implications for The Indonesian Healthcare Industry - Hidayat, Irwan (Jurnal Dinamika Manajemen, 2025)
This study aims to analyze the management branding of Sido Muncul products, especially the Tolak Angin product, in relation to the broader pharmaceutical industry in Indonesia. This research utilizes a systematic literature review (SLR) as a qualitative approach, supported by tools such as Publish or Perish, PRISMA, and Covidence softwareto collect, filter, and evaluate relevant academic sources. Additionally, a science mapping review serves as the quantitative approach, using Mendeley and VOSviewer software to visualize bibliometric data and research trends. Tolak Angin exemplifies effective brand management by successfully positioning itself as a trusted natural remedy within Indonesia’s competitive health landscape. The product’s strong market presence reflects strategic branding, consumer trust, and cultural relevance. The implications of Tolak Angin’s brand management go beyond individual success; it catalyzes broader shifts in Indonesia’s healthcare industry. As consumers increasingly prefer natural and holistic alternatives to synthetic drugs, Tolak Angin inspires other pharmaceutical companies to innovate and develop herbal-based remedies.